Pengaruh Kualitas Website BPS Kab. Siak Terhadap Kepuasan Pengguna Website Menggunakan Metode Webqual 4.0 - Nofirman Nofirman; Nizwardi Jalinus; Dedy Irfan (Universitas Negeri Padang, 2019)
This study aims to determine the influence of website quality of BPS Kab. Siak to the satisfaction of website users. In this study the quality of the website is measured by using webqual method. Webqual variables are independent variables consisting of ease of use, quality of information and quality of service interaction. The dependent variable is user satisfaction. The research method used in this research is quantitative correlation method. Sample selected from population of website user of BPS Kab. Siak, calculated using Slovin formula with 10% significance. To test the effect of the independent variable on the dependent variable using multiple linear regression analysis. This research resulted in a positive and significant influence of the three independent variables on user satisfaction, either partially or simultaneously.